Razões para Morar em Centros Históricos: O Caso de Belém (PA, Brasil) - Lobo, Marco Aurelio Arbage; Tourinho, Helena Lúcia Zagury; Morhy, Sâmia Saady (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2016)
Many historic centers of Brazilian cities undergo a physical degradation process of their buildings and public spaces, which often is accompanied by economic decline and reduction of residents. The Historic Center of Belem (HCB) also experiences a physical decline, but, unlike in other cities, it has maintained strong economic dynamism and moderate population growth. This work aims to identify the main socioeconomic characteristics of residents seeking to live in HCB and what are the main reasons leading them to live there, information that will be useful for the definition of a housing policy for occupation of existing vacant buildings in the area. To develop the work, data was collected from the 2010 population census and from a survey of 58 householders that rented or bought homes there in the past five years. The multinomial exact test was used as test of statistical significance. The results indicated that most of the residents who sought housing in the HCB have average levels of education, live in lower-middle class households and are self-employed. The proximity to workplaces and daily shopping were the two most cited reasons to live on the site. Furthermore, most of the respondents showed high levels of satisfaction about living in the HCB.